MORAL RIGHTS IN ROMANIAN AND IN FOREIGN CASE LAW - Ruxandra VIȘOIU (Challenges of the Knowledge Society)
Moral rights have always been a rather controversial subject in the field of copyright. Imposed in most countries around the world through the Berne Convention, recognized in most jurisdictions to certain degrees, but also partially rejected in others (most importantly, the US), moral rights have often been seen as the `black sheep` of intellectual property. But how did this concerning status affect the national and foreign jurisprudence on moral rights? In order to find out, we will analyse a few main court decisions, both from Romania and from other jurisdictions around the world and we will also make a couple of predictions about the potential future of moral rights in copyright law.